Public-Private Sector Wage Differentials by Type of Contract: Evidence from Spain - Raúl Ramos; Esteban Sanromá; Hipólito J. Simón Pérez (Institute for the Study of Labor (IZA), 2014)
The article examines public-private sector wage differentials in Spain using microdata from the Structure of Earnings Survey (Encuesta de Estructura Salarial). When applying various decomposition techniques, we find that it is important to distinguish by gender and type of contract. Our results also highlight the presence of a positive wage premium for public sector workers that can be partially explained by their better endowment of characteristics, in particular by the characteristics of the establishment where they work. The wage premium is greater for female and fixed-term employees and falls across the wage distribution, being negative for more highly skilled workers.
Keywords: C2; E3; J3; J4; 330; public-private sector wage gap; wage distribution; matched employer-employee data; decomposition methods